(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Nanotechnology has emerged as an advanced technology in the field of pharmaceutical sciences, offering innovative solutions to overcome the limitations of conventional drug delivery systems. Nanocarriers enable targeted and controlled delivery of therapeutic agents, improving drug efficacy and reducing adverse effects Objective: This presentation aims to discuss the role of nanotechnology in drug delivery, different types of nanocarriers, their applications, advantages, and challenges associated with their use in modern medicine. Methods: Various nanotechnology-based drug delivery systems, including liposomes, polymeric nanoparticles, dendrimers, micelles, and solid lipid nanoparticles, are reviewed based on their structure, drug-loading capacity, targeting ability, and therapeutic applications. Results/Discussion: Nanotechnology-based delivery systems enhance drug solubility, stability, bioavailability, and controlled release. They have shown promising applications in cancer therapy, gene delivery, vaccine development, and treatment of chronic diseases. These systems allow targeted drug action, minimizing damage to healthy tissues and improving patient outcomes. Conclusion: Nanotechnology represents a promising approach for the future of drug delivery by providing safer, more effective, and patient-specific therapies. However, challenges related to toxicity, manufacturing, cost, and regulatory approval need to be addressed for widespread clinical application.